2020
DOI: 10.3390/genes11121411
|View full text |Cite
|
Sign up to set email alerts
|

The Many Faces of DFNB9: Relating OTOF Variants to Hearing Impairment

Abstract: The OTOF gene encodes otoferlin, a critical protein at the synapse of auditory sensory cells, the inner hair cells (IHCs). In the absence of otoferlin, signal transmission of IHCs fails due to impaired release of synaptic vesicles at the IHC synapse. Biallelic pathogenic and likely pathogenic variants in OTOF predominantly cause autosomal recessive profound prelingual deafness, DFNB9. Due to the isolated defect of synaptic transmission and initially preserved otoacoustic emissions (OAEs), the clinical characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 73 publications
3
53
0
Order By: Relevance
“…Mutations in the gene OTOF encoding for the protein otoferlin cause hearing impairment with autosomal recessive inheritance, DFNB9 ( Yasunaga et al, 1999 ). To date, more than 200 pathogenic mutations have been identified in the OTOF gene ( Vona et al, 2020 ). While most mutations lead to profound deafness, a few non-truncating mutations result in mild to moderate progressive or temperature sensitive forms of hearing loss (reviewed in Vona et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the gene OTOF encoding for the protein otoferlin cause hearing impairment with autosomal recessive inheritance, DFNB9 ( Yasunaga et al, 1999 ). To date, more than 200 pathogenic mutations have been identified in the OTOF gene ( Vona et al, 2020 ). While most mutations lead to profound deafness, a few non-truncating mutations result in mild to moderate progressive or temperature sensitive forms of hearing loss (reviewed in Vona et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than 200 pathogenic mutations have been identified in the OTOF gene ( Vona et al, 2020 ). While most mutations lead to profound deafness, a few non-truncating mutations result in mild to moderate progressive or temperature sensitive forms of hearing loss (reviewed in Vona et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given no patients showed a positive OAE passed 5 years of age, we presume that the OAE response in OTOF-related ANSD disappears by 4-5 years of age at most, a little longer than previously thought. Related to the disappearance of OAE, some reports suggest that the disappearance of OAE could occur due to OHC damage originating from hearing aid use (Rouillon et al 2006;Vona et al 2020). On the other hand, it is also suggested that the use of hearing aids is not a de nitive factor for deterioration of OAE (Kitao et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…AAV-based gene therapy is considered to be a promising tool for actual human gene therapy due to its low immunogenicity, long-lasting transgene expression and ability to infect both dividing and non-dividing cells (Chandran et al 2017). At present, a few companies around the world are preparing for clinical trials using AAV (Akouos, Boston, MA, USA; Decibel Therapeutics, Boston, MA, USA; Sensorion, Montpellier, France) (Vona et al 2020). A new era of next-generation treatments for hereditary hearing loss, such as gene therapy, is certainly approaching; however, we should not forget that accurate treatment is based on accurate diagnosis and understanding of the clinical course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation